Spatial analysis of coral bleaching of developed area in Tioman Island - Nurfaika Muhamad; Anuar Ahmad, Anuar Ahmad; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2011